PENGEMBANGAN PARIWISATA BERKELANJUTAN BERBASIS SUBAK SEBAGAI BAGIAN WARISAN BUDAYA DUNIA UNESCO DI DESA MENGESTA KABUPATEN TABANAN - Herawati, Niluh (JURNAL MASTER PARIWISATA; Volume 02, Nomor 01, Juli 2015DO - 10.24843/JUMPA.2015.v02.i01.p05)
As part of the cultural landscape of Bali, UNESCO World CulturalHeritage, Mengesta village in Tabanan district has a variety ofnatural and cultural potentials that can be developed as touristattractions, including agricultural and its irigation system(subak). These can be managed properly in order to get benefitsfrom tourism economy. This study analysis the development ofsustainable tourism based on subak in the Mengesta village. Theresearch applied qualitative and quantitative approaches. Thestudy shows that subak has important and strategic position soit should be preserved in line with the objective of its designationas Word Cultural Heritage. However, the benefits of subak as aWorld Cultural Heritage have not been optimally perceived by thecommunity in relation to the development of sustainable tourismin the village of Mengesta. Only a small proportion of people whoenjoy the benefits of the status of subak as World Cultural Heritagein the context of tourism development. It is hoped that both thedistrict and provincial governments help the community throughfunding and setting up regulations so that the development ofsubak as tourist attraction can be improved while keeping itssustainability.
Keywords: Mengesta village, subak, world cultural heritage, sustainable tourism.